The Role of Grit In Indonesian Student - Maulana Arif Muhibbin; Ratna Sari Wulandari (Psychosophia: Journal of Psychology, Religion, and Humanity, 2021)
The current systematic review aims to investigate the role of grit in the Indonesian student setting. The search of the literature was conducted on two online databases, ScienceDirect and Google Scholar published between 2016 and 2020. There were seven studies identified using inclusive and exclusive selection criteria in this review. The primary findings demonstrated that grit has a positive influence on career decision-making and academic achievement. Perception of the father's involvement, the meaning of life, growth mindset, school wellbeing, self-control, and life satisfaction are known to have a significant positive correlation with grit. Finally, a positive variable such as self-efficacy can foster students' grit.